Digital transformation: a cross-level analysis of Canadian federal, provincial and municipal governments - Sperano, Isabelle; Chu, Vik; Andruchow, Robert (My University, 2024)
This article examines the state of digital transformation (DT) initiatives in all three levels of government across Canada. Data was collected from government websites, identifying 12 significant initiatives that pertain to the digital transformation of public service delivery. These initiatives were classified into five categories: strategy, guidelines and standards, open government portals, public communications, and digital units. This exploratory study reviews and analyzes the initiatives based on their geographical locations, revealing that the more populous provinces and territories have a more significant number of initiatives. Open data portals and visual guidelines and standards were found to be the most commonly implemented initiatives. This analysis aims to provide insights into government DT initiatives and practices and foster discussions for advancements in digital transformation strategies and digital service delivery to citizens.
Keywords: design; digital transformation; digital experience design; digital government; service design